Management of Clinically Significant Macular Edema - Elisa Taurisia; Ramzi Amin; AK Ansyori (Sriwijaya Journal of Ophthalmology, 2020)
Introduction: Macular edema is the most common cause of visual impairment in NPDR. Macular edema occurs due to increased perifoveal capillary permeability resulting in fluid accumulation in the macular area. Control of blood sugar levels is an important factor in the management of diabetic retinopathy because it can reduce the risk of progression of retinopathy, decreased vision and macular edema. Currently, focal photocoagulation argon lasers are the only proven long-term treatment for diabetic macular edema. Case presentation: Reported case of a 55-year-old woman, address outside the city, came to the Dr. Mohammad Hoesin General Hospital Palembang eye clinic with complaints of blurred vision since ± 6 months ago. three days ago, the patient went to an internal medicine clinic and was said to have high blood sugar and blood pressure. The views of both sufferers' eyes are increasingly blurred. The treatment chosen for this patient was intravitreal anti-VEGF (bevacizumab) injection in the right and left eye to reduce vascular permeability thereby reducing macular edema. 1-time bevacizumab injection has only a short-term optimal effect so re-injection is needed at 4-6 weeks intervals. Conclusion: A clinically significant case of macular edema (CSME) has been reported that is treated with intravitreal anti-VEGF combined with focal photon photocoagulation laser. The patient's final vision 1 week after the focal photocoagulation argon laser was performed showed improvement.